Elaboración de objetos de aprendizaje que incluye realidad aumentada en la unidad 1 de la asignatura de física del primer curso de bachillerato general unificado del colegio 27 de febrero de la ciudad de Loja, período 2016-2017 - Romero Paucar, Bladimir Stalin (2018)
The present investigative work arises from the problem reflected in students who present learning difficulties derived from the little interest and little attention to the classes in the subject of physics. Due to this problem, as a solution proposal, Learning Objects (LO) were developed using Augmented Reality (AR) as a mechanism of immersion in the learning process; The LO addresses issues such as: the average speed in the Uniform Rectilinear Movement (URM) and acceleration in the Uniformly Accelerated Rectilinear Movement (MRUA), also each LO has activities presented in 3D animations using AR. The LOs were developed on the basis of the APDDEI (Analysis and Procurement, Design, Development, Evaluation, Implementation) methodology, formally following each of its phases, coming to have as a product a valid and pertinent LO, after being completed and verified each of the phases was socialized LO, applying a data sheet validation to the physics teacher and BGU first-year students of the "27 de Febrero" School, obtaining very positive acceptance results. In conclusion, the LO comply with quality standards in the pedagogical, didactic and technological aspects, so they are didactic resources that will contribute greatly to the teaching process of the physics subject.